SISTEM INFORMASI INTERAKTIF PADA TRANSAKSI PULSA DENGAN MENGGUNAKAN SMS GATEWAY - Honggowibowo, Anton Setiawan (SENATIK STT Adisutjipto, 2013)
Information systems are generally used to support the viability of a business operation and management processes in an organization. To enhance the ability of information systems can be created an interactive information system, so it can provide rapid response and attractive to users. Interactive information system is more directed to the use of multimedia as a means of informing something. Multimedia is a combination of text, images, animations, sound and video. Various media are combined into a single unit of work will yield some information that has value that interactive communication is very high. The research will make a design of interactive information system on toll transaction using sms gateway. So the system can display the alarm and computer animated images on the screen when the computer is experiencing problems in the transaction pulse. In addition the system can also create video tutorial that shows step-by-step problem solving appropriate to the emergence of problems that occurred in the transaction pulse. With the information system interactive  it will help the operator pulses respond quickly to any problems in the credit transaction.